Provably sender-deniable encryption scheme - N.A. Moldovyan (Computer Science Journal of Moldova, 2015)
The use of the well known provably secure public-key cryptoscheme by Rabin is extended for the case of the deniable encryption. In the proposed new sender-deniable encryption scheme the cryptogram is computed as coefficients of quadratic congruence, the roots of which are two simultaneously encrypted texts. One of the texts is a fake message and the other one is a ciphertext produced by public-key encryption of secret message. The proposed deniable encryption method produces a ciphertext that is computationally indistinguishable from the ciphertext produced by some probabilistic public-key encryption algorithm applied to the fake message.